Wound infections following open reduction and internal fixation of calcaneal fractures with an extended lateral approach - Backes, Manouk (Springer Berlin Heidelberg, 2013)
PURPOSE: Post-operative wound infections (PWI) following calcaneal fracture surgery can lead to prolonged hospital stay and additional treatment with antibiotics, surgical debridement or implant removal. Our aim was to determine the incidence of superficial and deep PWI and to identify risk factors (RF). METHODS: This study is a retrospective case series. All consecutive patients from 2000 to 2010 with a closed unilateral calcaneal fracture treated with open reduction and internal fixation (ORIF) by an extended lateral approach were included. Patient, fracture, trauma and peri-operative characteristics were collected, including RF such as smoking, diabetes mellitus, time to operation, pre-operative in- or outpatient management and wound closure technique. The primary end point was a PWI as defined by the US Centers for Disease Control and Prevention. RESULTS: A total of 191 patients were included of which 47 patients (24.6 %) had a PWI; 21 (11.0 %) and 26 (13.6 %) patients had a superficial and deep wound infection, respectively. American Society of Anesthesiologists (ASA) classification higher than ASA 1 was associated with an increased risk. Placement of a closed suction drain at the end of surgery was associated with less PWI (35 % vs 15 %, p = 0.002). In this study, none of the previously reported RF were associated with an increased risk for PWI. CONCLUSIONS: ORIF of displaced calcaneal fractures is associated with a high rate of PWI of 25 %. Factors that were associated with an increased risk were ASA classification other than 1 and absence of a closed suction drain placement. A closed suction drain may be a protective measure to avoid wound complications.